Relative tolerance of linseed (Linum usitatissimum) varieties to dodder (Cuscuta Campestris) infestation - MISHRA, J S; MOORTHY, B T S; BHAN, MANISH (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted for 3 years from 2002- 03 to 2004-05 during winter season at Jabalpur, Madhya Pradesh to evaluate the relative tolerance of 14 linseed (Linum usitatissbnum L.) varieties against Cuscuta canzpestris, the stem parasite dodder. Different varieties varied significantly in their response to Cuscuta infestation in tenus ofplant height, branches/plant, capsules/plant, seeds/capsule, 1 OOO-seed weight and seed yield. Irrespective of the varieties Cuscuta infestation reduced the growth and yield attributes and seed yieId of linseed as compared to Cuscuta free conditions. Reduction in seed yield due to C. campestris in different varieties varied from 7.26%in 'Garima' to 44.29 %in 'J 23'; indicating 'Garima' as the most tolerant variety against C. campestris.